Trends and Outcomes in the Operative Management of Traumatic Vascular Injuries: A Comparison of Open versus Endovascular Approaches. Issue 5 (May 2017) - Richmond, Bryan K.; Judhan, Rudy; Sherrill, William; Yacoub, Michael; Aburahma, Ali F.; Knackstedt, Kimball; Chumbe, Julton T.; Samanta, Damayanti; Thompson, Stephanie N.
Controversy exists in vascular trauma regarding the best method of treatment—open versus endovascular techniques. Little has been published on this complex topic. Patients from 2005 to 2013 at a Level I trauma center with vascular injuries were identified via a prospectively trauma registry. Patient data, injury type/severity, treatment, and 30-day outcomes were obtained from the trauma registry and the chart review. Adverse events (limb loss, major disability, and death) were outcomes of interest. Univariate analysis and multivariate logistic regression were used to identify predictors of adverse events. In all, 346 patients were included (median age 34, range 1–93 years). Median Injury Severity Score (ISS) was 10(1–59). Endovascular repairs (n = 52) increased from 0 per cent (2005) to 32 per cent (2013), and demonstrated equivalent outcomes to open approaches (P = 0.24). On multi-variate analysis, higher ISS (P = 0.001), increasing age (P = 0.01), and lower extremity injuries (P = 0.001) were associated with adverse outcomes across the entire series. Endovascular approaches were most commonly used in vascular injuries of the chest/abdomen (39 of 52, 75% of all endovascular procedures in the series, P < 0.001), older patients(P = 0.003), blunt injury mechanism (P < 0.001), and patients with a higher ISS at presentation (P < 0.001). In conclusion, this large series, the use of endovascular procedures increased over time, and was associated with equivalent outcomes to open approaches, despite their higher usage in older patients, those with chest/abdominal injuries, and those with a higher ISS at presentation. Although these retrospective results are encouraging, further prospective study into the role of endovascular therapies in the treatment of vascular injuries.